Revision of the population structuring of Illex argentinus (Castellanos, 1960) and a new interpretation based on modelling the spatio-temporal environmental suitability for spawning and nursery - Crespi Abril, Augusto Cesar (2012)
During the last 30years, interpretation of the population structuring of Illex argentinus evolved from a single to a six-stock model, in which stocks are characterized by having distinct spawning seasons, areas and migration patterns. It is assumed that major spawning activity occurs in discrete pulses along the outer-shelf/slope off Argentina/southern Brazil during late-fall/winter and that early life stages develop near the Brazil-Malvinas Confluence (BMC). Nevertheless, there are inconsistencies in the delimitation of stocks and the interpretation of their life histories. Here, we developed a model based on records of seawater temperature and chlorophyll-a concentration to establish the quality of different areas of the species' geographic distribution as spawning and nursery grounds. Whereas the outer-shelf/slope domain south of 37°S presents marked seasonal restrictions for embryonic development and breeding, coastal areas within 44°-28°S are highly suitable most of the year. Squid in pre-spawning aggregations at the outer-shelf/slope south of 41°S would invest less energy to reach equally suitable spawning areas at the coast than at the BMC. Findings of paralarvae, stranded juveniles and mature squid in coastal areas off northern Patagonia support the predictions of the model. Based on these results, the population structuring and reproductive-migration patterns are reviewed and a new interpretation is proposed: Illex argentinus spawns not only in discrete seasons and areas on the slope and mid/outer shelf, but also conducts quasi-permanent spawning migrations to coastal areas, resulting in a more continuous pattern of recruitment than previously considered and in weak stock differentiation.